Characterization and Sliding Wear Behavior of Low-Pressure Cold-Spray Al-Al2O3 and Al-Al2O3/TiN Composite Coatings - Pudsadee Chupong; Mahathep Sukpat; Karuna Tuchinda (Metals, 2025)
Low-pressure cold-spray (LPCS) aluminum is widely used for coating depositions in various engineering applications but is limited by its low hardness and poor wear resistance. To improve these properties, ceramic particles are added to form metallic matrix composites (MMCs). High-pressure processes can achieve effective MMC coatings but are costly and energy intensive. LPCS has been studied to develop an Al-based MMC at a lower cost. To ensure the adaptation of developed LPCS coating in engineering applications, the behavior of the coating under certain loads needs to be established. This study investigates the sliding wear behavior, friction characteristics, hardness, and microstructure of Al-Al2O3 and Al-Al2O3/TiN composite coatings deposited using LPCS at 1 MPa and 450 °C. The effect of adding 25 wt% TiN to the Al-Al2O3 composite was explored. Although the addition of TiN did not significantly enhance the hardness of the coating, SEM analysis revealed notable differences in wear behavior between the two coatings. The Al-Al2O3/TiN composite exhibited better wear resistance, which was attributed to the reduced formation of powdery wear debris and improved crack suppression. These findings highlight the potential of TiN reinforcement to enhance the tribological performance of LPCS aluminum-based coatings, offering a promising solution for improving wear resistance in engineering applications.